Tanggung Jawab Hukum Tokopedia Terhadap Konsumen Atas Ketidaksesuaian Barang Dalam Jual Beli Online - Rahmawati, Zahra (UIN Syarif Hidayatullah Jakarta, 2024)
This study discusses Tokopedia's legal responsibility towards consumers for non-conformity of goods in online sales transactions. Although regulations regarding electronic commerce have been established, there are still weaknesses in consumer legal protection. Consumers often experience losses due to goods received that do not match the description without receiving proper compensation. This study uses a normative-empirical method with a regulatory-statutory approach and case studies to analyze Tokopedia's responsibility and legal protection for consumers in electronic transactions. The study results indicate that the available settlement mechanisms, such as online dispute resolution, have not fully provided justice for consumers. Tokopedia, as a platform provider, is responsible for ensuring that consumer rights are protected and providing more effective settlement solutions. In addition, consumer legal awareness of their rights in electronic transactions is still low, so they are willing to take their position in dealing with sales with sellers. This study highlights the need to strengthen regulations and implement more effective consumer legal protection in the e-commerce ecosystem. An active role is needed from the government and e-commerce platforms to ensure a transparent complaint mechanism supporting consumer protection to create a safer and fairer digital trade ecosystem.